PERILAKU CROSS-LAMINATED TIMBER (CLT) SEBAGAI MATERIAL UTAMA BANGUNAN TINGKAT MENENGAH TAHAN GEMPA DI INDONESIA - Ika Rahmawati Suyanto (Rekayasa Sipil, 2020)
Cross-laminated timber (CLT) is made up of multilayered timber stacked perpendicularly, which improved the dimensional stability and allowing CLT to has high bearing capacity in its two direction. Despite all the advantages, CLT has not yet gain much attention in Indonesian, especially the utilization in mid-rise building construction. In order to have a better understanding about CLT as main structural element, the behaviour of mid-rise building made of CLT was assessed by running a 3D model of 5-story building by combining building code in Indonesia with CLT parameter from previous researcher as well as recommended adjustment from previous researchers. The research shows that CLT building statisy the allowable parameter for mid-rise building in Indonesia.